Analysis of Indonesian Language Learning on Poetry Writing Skill in Elementary Schools - Utami, Nindya Chandra Muji; Harefa, March Markus; Pudjiati, Indri; Fitriani, Lilik (STKIP Singkawang, 2024)
This study will be studied about learning Indonesian the ability to write poetry in elementary school using the Mind Mapping technique, reviewed from various research articles that discuss the same topic. Articles, articles displayed, discussions, and conclusions. This research uses Narrative Literature Review (NLR) method model with the Compare technique. The data is collected through articles from national journals published during the previous nine years served as the study's data sources from 2014 to 2022. The findings showed that the articles on poetry writing skills in elementary schools consisted of 4 articles analyzed from the type of Classroom Action Research. Its implementation is by the theoretical frameworks that have been cited. Finding a connection between two articles on the same issue makes this study innovative. The findings of the study analysis indicated that the classroom action research technique was the approach most frequently employed to evaluate poetry writing abilities in elementary schools.